Review of the genus Pleurotroppopsis Girault (Hymenoptera: Eulophidae) with interspecific phylogenetic relationships based on morphological characters - Cao, Huan-Xi; Dale-Skey, Natalie; Burwell, Chris J.; Zhu, Chao-Dong (Zootaxa, 2022)
This study is dedicated to the late Dr. John LaSalle, and reviews the world species of Pleurotroppopsis Girault (Hymenoptera: Eulophidae); fourteen species are treated, of which two are newly described: P. dactylispae Cao & Zhu sp. nov. from China and P. peukscutella Cao & Zhu sp. nov. from Malaysia. On the basis of morphological characters, tentative relationships among genera allied to Pleurotroppopsis are discussed. A revised definition of Pleurotroppopsis is presented based on study of type specimens of all species and a critical review of previous studies on the genus. In addition, parsimony analyses were conducted to infer a phylogeny of Pleurotroppopsis species based on a unique data matrix of morphological characters. Keys to genera allied to Pleurotroppopsis and to known species of Pleurotroppopsis are provided.